Navigating Through Innovation in Elderly’s Health: A Scoping Review of Digital Health Interventions - Macarena Hirmas-Adauy; Carla Castillo-Laborde; Camila Awad; Anita Jasmen; Maurizio Mattoli; Xaviera Molina; Andrea Olea; Isabel Matute; Fernando Soto; Paola Rubilar; Oscar Urrejola; Oscar Urrejola; et al. (Public Health Reviews)
ObjectivesComprehensively map and summarize digital health initiatives for the elderly and caregivers.MethodsScoping review between April and May 2022 based on Joanna Briggs methodology. Databases used included PubMed, Cochrane Library, CINAHL Plus, and Web of Science, along with grey literature and hand searches. Two reviewers independently conducted screening and eligibility phases, with a third resolving disagreements. Data were thematically analyzed.ResultsThe review included 421 documents. Most documents were published between 2013 and 2022, with a recent increase. Most studies, originating from high-income countries, focused on home applications and were mainly in the testing and validation stages. Telephones and computers were the predominant devices. Health objectives included monitoring, prevention, and treatment, with interventions utilizing directed communication and personal health monitoring for individuals, and telemedicine and decision support for healthcare providers.ConclusionIncreasing integration of technology in older adults’ lives, along with their increasing proficiency, is driving a significant rise in digital health interventions. Despite this growth, further research in middle- and low-income countries, for caregivers and evaluating effectiveness and feasibility of these technological interventions is needed.